2007
DOI: 10.1002/joc.1554
|View full text |Cite
|
Sign up to set email alerts
|

The storm morphology of deadly flooding events in the United States

Abstract: This study investigates the synoptic and mesoscale environments associated with deadly flooding events in the United States from 1996 to 2005. A manual environment classification scheme, which includes analyses of surface charts, 500 hPa maps, and composite radar data (where available), is utilized to ascertain the primary ascent mechanisms and storm types producing these fatal flood events. Of the ten classifications in the scheme, the two most dominant ascent mechanisms associated with deadly floods include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…Changnon and D. Changnon 1999;Curran et al 2000;Ashley and Mote 2005;Ashley and Ashley 2008a, b;and Gall et al 2009) because of the underreporting of both casualties and damage estimates. However, as also noted by Ashley and Ashley (2008b), fatal weather events are more likely to be reported due to enhanced media attention. Therefore, Storm Data provides researchers with an adequate first estimate of the actual number of fatalities for given oceanic and atmospheric events.…”
Section: Fatality Catalog Compilationmentioning
confidence: 75%
“…Changnon and D. Changnon 1999;Curran et al 2000;Ashley and Mote 2005;Ashley and Ashley 2008a, b;and Gall et al 2009) because of the underreporting of both casualties and damage estimates. However, as also noted by Ashley and Ashley (2008b), fatal weather events are more likely to be reported due to enhanced media attention. Therefore, Storm Data provides researchers with an adequate first estimate of the actual number of fatalities for given oceanic and atmospheric events.…”
Section: Fatality Catalog Compilationmentioning
confidence: 75%
“…These contingencies may explain why Changnon and Hewings (2001) found that annual measures of the areal extent of the United States experiencing heavy precipitation were poorly correlated with annual US flood losses from 1950 to 1997 -despite significant upward trends in both heavy precipitation events and flood losses over the same period. Most US flood fatalities have been associated with heavy rainfall events: Ashley and Ashley (2008a) reported that 88% of flood-related fatalities across the contiguous United States from 1996 to 2005 (exclusive of hurricane Katrina) were due to flash floods or tropical system floods; Ashley and Ashley (2008b) similarly found that flash floods and tropical system floods were the deadliest flood types in the contiguous United States from 1959 to 2005. Flood deaths due to flashy precipitation peaked in the summer to early fall (Ashley & Ashley, 2008a); flash flood fatality rates were highest in Southwestern and South Central states, the Ozarks, and the Appalachians from Tennessee to Pennsylvania (Ashley & Ashley, 2008b).…”
Section: Extreme Rainfallmentioning
confidence: 97%
“…Extreme rainfall often affects society through flooding, and studies have found strong connections between heavy rainfall events and increased peak streamflow (Changnon & Demisse, 1996;Robinson, 2003) and between heavy rainfall and flood events (Ashley & Ashley, 2008a). However, physical geographers have stressed that this connection between heavy rainfall and floods is heavily contingent on the local geography of affected basins, including land-use and drainage (Changnon & Demisse, 1996), and seasonality, soil moisture, and precursor events (Robinson, 2003).…”
Section: Extreme Rainfallmentioning
confidence: 98%
See 2 more Smart Citations